Galaxies in Turmoil The Active and Starburst Galaxies and the Black Holes That Drive Them - Kitchin, C. R. (Springer London : Imprint: Springer, 2007)
Active galaxies involve some of the most extreme conditions and some of the most intriguing phenomena found anywhere in the universe. Written for amateur astronomers, school and college science students and for those with a more general interest in science, Galaxies in Turmoil provides a readable, non-mathematical account of one of the hottest areas of astronomical research. Observing details are given for 160 active galaxies, all of which are within the reach of amateur astronomers using small to medium-sized telescopes. There are tips on observing galaxies and active galaxies using binoculars and small to medium telescopes, along with a guide to imaging galaxies with CCD cameras. Galaxies in Turmoil is equally suitable for practical amateur astronomers, or as a text for college courses including galaxies, active galaxies, quasars, deep-space objects and large-scale astronomy, up to the final year of an astrophysics, physics or science degree. Research students - and even established research astronomers - will also find this book invaluable as a quick reference to the properties of, and phenomena within, those types of active galaxies that may be outside their specialisms.